Density constrains cascading consequences of warming and nitrogen from invertebrate growth to litter decomposition. Issue 7 (1st July 2016) - Hines, Jes; Reyes, Marta; Gessner, Mark O.
Abstract: Smaller invertebrate body mass is claimed to be a universal response to climate warming. It has been suggested that body mass could also predict consumer influences on ecosystem processes in a warmer world because generalized rules describe relationships between body mass, temperature, and metabolism. However, the utility of this suggestion remains tenuous because the nutritional and physiological constraints underlying relationships between body mass and consumer‐driven processes are highly variable in realistic settings. Here we test, using a generalist invertebrate detritivore, fungi, and leaf litter, the limitations imposed by nutrition on growth and decomposition in response to global change. Strong competition for fungal food resources limited invertebrate growth and reduced body mass plasticity in response to warming and nitrogen pollution scenarios. When competition was relaxed by experimentally reducing invertebrate density, consumption of fungi promoted rapid invertebrate growth and enhanced invertebrate sensitivity to the global change scenarios, especially warming and nitrogen pollution together. Accordingly, fungi promoted invertebrate body mass plasticity and mediated consumer effects on decomposition causing the relative influence of warming and nitrogen pollution to vary across trophic levels. An important implication is that managing nitrogen pollution may alter which trophic level is most sensitive to warming.